Experimental mouse models for translational human cancer research - Zhou, Yinxi; Xia, Jinghua; Xu, Shuonan; She, Tao; Zhang, Yanning; Sun, Ying; Wen, Miaomiao; Jiang, Tao; Xiong, Yanlu; Lei, Jie (Frontiers in Immunology, 2023)
The development and growth of tumors remains an important and ongoing threat to human life around the world. While advanced therapeutic strategies such as immune check point therapy and CAR-T have achieved astonishing progress in the treatment of both solid and hematological malignancies, the malignant initiation and progression of cancer remains a controversial issue, and further research is urgently required. The experimental animal model not only has great advantages in simulating the occurrence, development, and malignant transformation mechanisms of tumors, but can also be used to evaluate the therapeutic effects of a diverse array of clinical interventions, gradually becoming an indispensable method for cancer research. In this paper, we have reviewed recent research progress in relation to mouse and rat models, focusing on spontaneous, induced, transgenic, and transplantable animal tumor models, to help guide the future study of malignant mechanisms and tumor prevention.